The students’ ability of writing report based on field study result in conservation area - Bhakti Karyadi; Pani Aswin (Journal of Science Education Research, 2019)
Important writing skills need to be enhanced to help students compete in the 4.0 educational era. The aim of this study is to describe the ability to write the results of field studies in the Panjang beach TWA area. Data collection techniques used are rubrics. The research instrument used was the rubric sheet assessing scientific reports. The results of this study indicate aspects of writing skills, namely score 3 category for the aspects of title, method, results, conclusions, bibliography, while score 2 with category of sufficient is obtianed for the aspects of introduction and discussion. The average score in the ability of students to write reports is 3 with a category of good via utilizing the field of study activities. Empowering writing skills can be done by innovating learning using outdoor learning.